Evaluating the Global Intensive Feeding Therapy (GIFT) for Children with CHARGE Syndrome: A Quasi-Experimental Study - Antonella Cerchiari; Francesca Pizza; Giorgia Biondo; Carolina Giordani; Martina De Paolis; Gessica Della Bella; Massimiliano Raponi; Marco Tofani (Children)
Background: This pilot investigation aimed to evaluate the efficacy of Global Intensive Feeding Therapy (GIFT) on feeding and swallowing abilities in children with CHARGE Syndrome (CS). GIFT is a novel rehabilitation program designed to leverage the principles of neuroplasticity, intensity, individualized treatment, and ecological validity. The program comprises 15 sessions conducted over one week, with sessions delivered three times per day. Methods: GIFT was preliminarily implemented in a cohort of seven children diagnosed with CS. To assess the risk of dysphagia, the Pediatric Screening–Priority Evaluation Dysphagia (PS-PED) was administered. The effectiveness of the intervention was evaluated using three instruments: the Karaduman Chewing Performance Scale (KCPS) for chewing performance, the American Speech-Language-Hearing Association National Outcome Measurement System (ASHA NOMS) for overall feeding abilities, and the Feeding Assessment Scale (FAS) to capture parents’ perceptions. Data were collected at baseline (T0), immediately post-intervention (T1), and at a six-month follow-up (T2). The Wilcoxon signed-rank test was employed for statistical analysis, and effect sizes for specific outcomes were determined using Kendall’s W. Results: The findings indicated that children with CS were at a high risk of dysphagia as measured by the PS-PED at baseline. Statistically significant improvements in chewing performance were observed at the six-month follow-up (p < 0.05). Feeding abilities, as measured by the ASHA NOMS, showed significant enhancement immediately post-intervention (p = 0.02) and at the follow-up (p = 0.03). Similarly, parents reported significant improvements in their children’s feeding abilities at both post-intervention and follow-up assessments (p = 0.02), further corroborating the clinical benefits of the intervention. Conclusions: These preliminary results suggest that GIFT may be an effective rehabilitation program for addressing feeding and swallowing disorders in children with CS. Further studies with larger sample sizes and controlled designs are warranted to substantiate these findings and refine the intervention protocol.